2013
DOI: 10.1152/ajpheart.00570.2012
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 promotor hypermethylation and STAT3-NF-κB interaction downregulate SOCS3 expression in human coronary artery smooth muscle cells

Abstract: Agrawal DK. SOCS3 promotor hypermethylation and STAT3-NF-B interaction downregulate SOCS3 expression in human coronary artery smooth muscle cells. Am J Physiol Heart Circ Physiol 304: H776 -H785, 2013. First published January 18, 2013 doi:10.1152/ajpheart.00570.2012.-Suppressor of cytokine signaling-3 (SOCS3) is an intracellular negative regulator of cytokine signaling pathway. We recently found significant reduction in SOCS3 expression in coronary artery smooth muscle cells (CASMCs) of atherosclerotic swine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 52 publications
(45 reference statements)
2
45
0
Order By: Relevance
“…In HCASMCs, we reported that only IGF-1 treatment, but not TNF-α, induces activation of STAT3, whereas NF-κB was activated only in response to TNF-α treatment, but not IGF-1, and the co-immunoprecipitation results showed the binding of activated STAT3 to NF-κB in the cells that were treated with both TNF-α and IGF-1 [10]. These results not only suggest that SOCS3 expression was pre-transcriptionally inhibited, but it also essentiates the role of canonical JAK/STAT/NF-κB pathway in regulating SOCS3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HCASMCs, we reported that only IGF-1 treatment, but not TNF-α, induces activation of STAT3, whereas NF-κB was activated only in response to TNF-α treatment, but not IGF-1, and the co-immunoprecipitation results showed the binding of activated STAT3 to NF-κB in the cells that were treated with both TNF-α and IGF-1 [10]. These results not only suggest that SOCS3 expression was pre-transcriptionally inhibited, but it also essentiates the role of canonical JAK/STAT/NF-κB pathway in regulating SOCS3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that SOCS3 expression was dramatically decreased in porcine coronary artery smooth muscle cells (PCASMCs) in presence of TNF-α and IGF-1 [9]. We also showed that the SOCS3 promoter region was methylated when human coronary artery smooth muscle cells (HCASMCs) were treated with both TNF-α and IGF-1, which resulted in the inhibition of SOCS3 expression [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory has found a significant reduction in SOCS3 expression in the neointimal lesion after balloon angioplasty in coronary arteries of atherosclerotic swine (52). In addition, our laboratory demonstrated that hypermethylation of the SOCS3 gene in SMCs could be an underlying mechanism of intimal hyperplasia and restenosis, suggesting that inhibition of SOCS3 promoter methylation is a potential anti-neointimal hyperplasia target (53).…”
Section: Antineointimal Hyperplasiamentioning
confidence: 80%
“…Smooth muscle cells Intimal hyperplasia and restenosis [15] Mitofusin-2 [16] Extracellular superoxide dismutase Cell-specific expression; protection from oxidative stress and modulation of vascular tone [17] Sixth CTCF-binding site upstream of H19; insulin like growth factor-2…”
Section: Histone Methylationmentioning
confidence: 99%